FABRICA: A Bioreactor Platform for Printing, Perfusing, Observing, & Stimulating 3D Tissues - Smith, Lester J. (Sci Rep, 2018)
We are introducing the FABRICA, a bioprinter-agnostic 3D-printed bioreactor platform designed for 3D-bioprinted tissue construct culture, perfusion, observation, and analysis. The computer-designed FABRICA was 3D-printed with biocompatible material and used for two studies: (1) Flow Profile Study: perfused 5 different media through a synthetic 3D-bioprinted construct and ultrasonically analyzed the flow profile at increasing volumetric flow rates (VFR); (2) Construct Perfusion Study: perfused a 3D-bioprinted tissue construct for a week and compared histologically with a non-perfused control. For the flow profile study, construct VFR increased with increasing pump VFR. Water and other media increased VFR significantly while human and pig blood showed shallow increases. For the construct perfusion study, we confirmed more viable cells in perfused 3D-bioprinted tissue compared to control. The FABRICA can be used to visualize constructs during 3D-bioprinting, incubation, and to control and ultrasonically analyze perfusion, aseptically in real-time, making the FABRICA tunable for different tissues.